Product differentiation by marketing and processing cooperatives: A choice experiment with cheese and cereal products. Issue 4 (18th February 2018) - Grashuis, Jasper; Magnier, Alexandre
Abstract: With ongoing consolidation of food retailers and segmentation of consumer preferences, agri‐food producers and manufacturers have increased motivation to pursue product differentiation. We study if and how farmer cooperatives can build brand equity to drive or support product differentiation. With emphasis on ownership type and product origin, we conduct two choice experiments with cheese and cereal consumers in the United States. The results of our multinomial logit model indicate farmer cooperatives can command a price premium as compared to store brands, but not as much as non‐cooperatives. Cheese and cereal consumers also indicate a general willingness to pay for product origin and family ownership attributes, but the effects are not always compatible with farmer cooperatives. Overall, although price premiums for cooperative brands and labels may exist across various product categories, the heterogeneity in willingness to pay estimates for other product attributes is suggestive of the difficulties farmer cooperatives face in pursuit of product differentiation. [EconLit citations: Q11, Q13, M30]